Water pinch analysis evolution towards a holistic approach for water minimization - Abdul Manan, Zainuddin (Curtin University of Technology and John Wiley & Sons Ltd., 2007)

(untitled)
This paper reviews the evolution in water pinch analysis (WPA) research and development efforts toward a holistic and sustainable management of water resources. The paper provides a critical review of the four key areas related to the development of WPA - setting the minimum water flow rate targets, network design to achieve the targets, improvement of water networks through process change techniques and design of cost-effective water networks. The current gaps in WPA research, the role of the urban water pinch and the holistic minimum water network technique in bridging the water pinch technology gaps are the highlights of the paper